The Mustahik Zakat in Various Dimensions of Fiqh in Era Society 5.0 - Desi Refnita (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2021)
This article will discuss mustahik zakat, who are the groups who will receive